Penanganan Kolam Sedimentasi Hasil Pencucian Bauksit Di PT. ANTAM Tbk. Tayan - Muhammad Ridho; Peter Eka Rosadi (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2018)
Bauxite ore mining PT.Antam Tbk. located in Tayan Hilir Subdistrict, Sanggau Regency, West Kalimantan Province is an open pit backfilling system. Besides the bauxite ore extraction, the washing process resulted slurry which is entering the open channel towards the sedimentation pond. This study aims to determine the total discharge of slurry that will enter the sedimentation pond and assess the capacity of existing sedimentation ponds. The results showed that based on the production target of 700,000 tons of Bauxite Washed/year with 60% concretion factor data, the total discharge of water entering the sedimentation pond was 3.54 m3/sec. The slurry from the open channel will go into the sedimentation pond so that the deposition found in Segment I, IV, V, and VI was 409.06 m3/day, 254.59 m3/day, 561.35 m3/day, and 273.90 m3/day respectivelly. Intensive dredging material will be carried out using two Hitachi Zaxis 210 LC Long-Arm Excavator units. The cleaning time needed by Segment I, IV, V, and VI are 10 days, 6 days, 9 days and 5 days, so that the dredging time of Segment I, IV, V, and VI are 82 days, 65 days, 53 days and 62 days respectivelly